First isolation and genomic characterization of bovine parechovirus from faecal samples of cattle in Japan. (9th February 2022) - Oba, Mami; Sakaguchi, Shoichi; Wu, Hong; Fujioka, Yoshihiko; Takemae, Hitoshi; Oki, Hisako; Kawai, Megumi; Shiokawa, Mai; Aoki, Hiroshi; Fukase, Yuka; Madarame, Hiroo; Nakano, Takashi; et al.
Abstract : A novel picornavirus was isolated from the faeces of a diarrhoeic cow using MA-104 cells at the third blind passage. This virus, named Den1/2021/JPN, was completely sequenced using total RNA from the cell culture supernatant by deep sequencing. The genome of Den1/2021/JPN had a standard picornavirus genome organisation with conserved picornaviral motifs. The 5′ untranslated region harboured a type-II internal ribosomal entry site. Den1/2021/JPN was most closely related to a bovine parechovirus (Bo_ParV) named cow/2018/4, which has been recently identified in publicly available databases. Phylogenetic analyses and pairwise sequence comparison revealed that Den1/2021/JPN and Bo_ParV cow/2018/4 clustered with parechoviruses and were most closely related to Parechovirus E identified in birds of prey, exhibiting nucleotide sequence similarity of 64.2–64.5 %, 58.6–59.7 % and 66.3–66.4 % in the polyprotein, P1 and 2C+3 CD coding regions, respectively. This study presents the first report on the isolation of Bo_ParV. Den1/2021/JPN and Bo_ParV cow/2018/4, which are candidates for a novel species in the genus Parechovirus .